Pengembangan Learning Management System (LMS) Menggunakan Moodle Pada Fase E di SMAN 1 Lubuk Alung - Usman, Shelby; Rahmi, Ulfia; Hendri, Nofri; Pratiwi, Rahmi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to increase student engagement in learning through the development and implementation of interactive features on Moodle. Some of the features developed include quizzes, interactive discussion forums, and learning videos. This type of research is Research and Development with a 4D development model. Research data was collected through questionnaires and validation sheets. Data analysis was carried out in a quantitative descriptive manner to determine the level of student involvement and the quality of the LMS. At the development stage, validation tests were carried out by four validators, three media validators and one material. A practicality trial was carried out on Phase E students of SMAN 1 Lubuk Alung totaling 36 students to test the practicality of the LMS developed. The assessment results from the material validators received an average score of 4.6 with the category